Investigation into geothermal-driven dual-temperature district heating substation and its performance under variable conditions - LI Tiancheng; SHI Wenxing; WANG Baolong (Xi'an Gongcheng Daxue xuebao)
High-temperature geothermal energy is precious renewable resource for heating. Reducing the return temperature of geothermal water is an important way to maximize geothermal heating potential and expand the heating area. Considering that existing buildings generally use high-temperature radiators and other heating terminals, while newly constructed buildings mostly use low-temperature floor heating terminals, the required supply water temperatures for these two types differ. In response to this, a geothermal energy-driven dual-temperature district heating substation system with a single absorption heat pump and two heat exchangers is proposed. This system aims to produce dual-temperature hot water for both high-and low-temperature heating terminals and reduce the return temperature of geothermal water. Simulation results show that when the geothermal outlet water is 100 ℃, and the secondary network's high- and low-temperature terminal supply water temperatures are 50 ℃ and 35 ℃ respectively, the return temperature of geothermal water in the dual-temperature district heating substation one can be reduced to 20.1 ℃. Compared to a substation using two serial heat exchangers, the proposed one can lower the geothermal water return temperature by 14.9 ℃, reduce the geothermal water flow rate by 18.6%, and improve COP by 11%, demonstrating significant energy-saving advantages. Variable working condition analysis indicates that promoting the use of low-temperature heating terminals helps further reduce the return temperature of geothermal water, increase the heat supply to users, and improve the COP of the dual-temperature district heating substation.